Auditoría de gestión administrativa-financiera y su incidencia en la rentabilidad de la compañía Haciencorp. S.A. del cantón Buena Fe provincia de Los Ríos, año 2013 - Vélez Salvatierra, Betsy Yicenia (2015)
This entitled "Audit of administrative and financial management and its impact on the profitability of the Company HACIENCORP. Inc. cantón Buena Fe province of Los Ríos, 2013", was held in order to put into practice the knowledge acquired during the different modules received in the unit distances from the State Technical University Quevedo, and is clearly provide valuable information the General Manager to make the necessary corrections. The audit was based on four important objectives such as; investigate the current situation of administrative and financial management, analyze the level of profitability and the degree of trust accounting records, verifying compliance with laws and standards employed in the company and make a final report. This work was gotten by applying methods, types and research techniques, the same who facilitated the search, investigation and collection of primary and secondary data in order to achieve the objectives. The research results showed that; the current situation of administrative and financial management of the Company HACIENCORP SA It is suitable as 100% of employees surveyed who said they were satisfied with the work done. As for the level of trust accounting records as components Coso I like is 72%, which is within the high weighting, while the level of risk to 28%. The degree of compliance with laws and regulations applicable to the Company is higher than 100%, and yes are employed in the company IAS and ISA NIIFF, internal regulations and labor law. The final audit report on administrative and financial management presents the findings with their respective criteria, causes, effects and recommendation for the authorities to make the best decisions in the case.